Paeciloside A, a New Antimicrobial and Cytotoxic Polyketide from Paecilomyces sp. Strain CAFT156 - Talontsi, Ferdinand Mouafo; Nwemeguela Kenla, Timothee J.; Dittrich, Birger; Douanla-Meli, Clovis; Laatsch, Hartmut (Planta Medica, 2012)
Paeciloside A (1) and eight known compounds, acremoauxin A (2), farinosones A (3) and B (4), 1,5-dideoxy-3-C-methyl-arabitol (5), ergosterol, ergosterol peroxide, cerebroside C, and adenosine, were isolated from cultures of Paecilomyces sp. CAFT156, an endophytic fungus occurring in Enantia chlorantha Oliv (Annonaceae) leaves. The structure of the new compound 1 was elucidated using MS, UV, 1D and 2D NMR experiments, while its absolute configuration was established by subsequent single-crystal X-ray diffraction analysis using copper Kα radiation and invariom nonspherical scattering factors. Paeciloside A (1) and compounds 2, 4, and 5 displayed inhibitory effects on two gram-positive bacteria, Bacillus subtilis and Staphylococcus aureus at a concentration of 40 µg per paper disk and moderate cytotoxicity towards brine shrimp larvae (Artemia salina). This study presents the first report on an endophytic fungus isolated from E. chlorantha Oliv and its natural products.
Keywords: Enantia chlorantha; Annonaceae; Paecilomyces sp.; Trichocomaceae; antimicrobial; cytotoxicity